(untitled) (Academicia Globe: Inderscience Research, 2021)
The article studies proper names, which are obligatory in fairy-tale discourse and are cognitively, semantically and communicatively charged. Cognitive way of studying functional and pragmatic features of proper names in English fairy-tale discourse reveals semantic meaning and pragmatic orientation of proper names as transferring units of cognitive information.